Pemberdayaan Kader PKK Kelompok Wanita Tani Melalui Program Pemanfaatan Limbah Plastik Menjadi Kerajinan Tangan Bunga Plastik (BUTIK) di Desa Karanglo, Kecamatan Kunir, Kabupaten Lumajang - Basuki; Nainggolan, Jeremia Rade Mikhael; Efendi, Teguh; Dewi, Vininda Febri Rismana (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
One of the problems that is currently being highlighted in the community regarding environmental comfort is waste, both plastic waste, household waste, and waste in general. Waste management is carried out by instilling a sense of concern for the environment through a program of making handicrafts from plastic waste into plastic flowers, which have aesthetic value and high economic value as a means of creative economy based on entrepreneurship by optimizing the empowerment of the role of PKK cadres in Karanglo Village. This program aims to help reduce the volume of plastic waste in Karanglo Village in order to maintain ecological environmental balance. This program is implemented in the form of direct socialization and training for PKK cadres in Karanglo Village. This program has a direct impact on reducing the amount of plastic waste, increasing social networks among PKK cadres, and becoming a source of additional income for the community.